AORTIC AND SUPERIOR MESENTERIC ARTERY THROMBOSIS IN ANTITHROMBIN III DEFICIENCY-DIAGNOSTIC AND THERAPEUTIC CHALLENGES IN CONSERVATIVE MANAGEMENT - Dimitrije, Surla; Nikolić, Marija; Trifunović, Nemanja; Stojadinović, Milica (Sanamed, 2025)
Introduction: Thrombosis of large arterial vessels, such as the abdominal aorta and superior mesenteric artery, is a rare but serious condition that requires timely diagnosis and appropriate management. One of the risk factors is antithrombin III (AT III) deficiency, a rare coagulation disorder that increases the likelihood of thrombosis. While arterial thromboses are less common than venous ones, they can have significant clinical consequences. Case report: We present the case of a 39-year-old woman hospitalized due to sudden abdominal pain. Diagnostic imaging, including a contrast-enhanced CT scan of the abdomen and pelvis and CT angiography, revealed thrombosis of the distal abdominal aorta and superior mesenteric artery. Laboratory testing confirmed low AT III levels, while tests for hereditary thrombophilias were negative, suggesting a likely acquired deficiency. The patient was treated conservatively with AT III concentrate, low-molecular-weight heparin, and oral anticoagulation, alongside regular INR monitoring. Therapy was complemented with cardioprotective and gastroprotective medications, as well as physical rehabilitation. During hospitalization, the patient remained hemodynamically stable, and symptoms gradually resolved. Follow-up imaging after several months demonstrated complete recanalization of the affected vessels. Long-term monitoring over two years confirmed stable clinical status and absence of recurrent thrombosis. Conclusion: This case highlights the importance of early diagnosis, identification of the underlying cause, and carefully implemented conservative management in patients with AT III deficiency. It demonstrates that even in extensive arterial thrombosis, conservative management can preserve organ function and achieve a favorable outcome without the need for surgical intervention.